Metabolomic Insights into Volatile Profiles and Flavor Enhancement of Spice-Smoked Chicken Wings - Yajiao Zhao; Ye Guo; Danni Zhang; Quanlong Zhou; Xiaoxiao Feng; Yuan Liu (Foods)
Traditional smoking techniques, while historically valued for preservation and flavor enhancement, face limitations in aromatic diversity and safety, prompting exploration of spice-derived alternatives to meet modern culinary demands. This study explores the volatile compound profiles and aroma modulation of chicken wings smoked with four spices—cardamom, rosemary, mint, and rose—using a novel, household-friendly smoking protocol. The method combines air fryer pre-cooking (180 °C, 16 min) with electric griddle-based smoke infusion, followed by HS-SPME/GC-TOF/MS, relative odor activity value (ROAV) calculations, and metabolomic analysis. A total of 314 volatile compounds were identified across five samples. Among them, 45 compounds demonstrated odor activity values (ROAV) ≥ 1, contributing to green, woody, floral, and sweet aroma attributes. Eucalyptol displayed the highest ROAV (2543), underscoring its dominant sensory impact. Metabolomic profiling revealed a general upregulation of differential volatiles post-smoking: terpenes were enriched in wings smoked with cardamom, rosemary, and mint, while aldehydes and alcohols predominated in rose-smoked samples. An integrated screening based on ROAV and metabolomic data identified 24 key volatiles, including eucalyptol, β-myrcene, methanethiol, and α-pinene, which collectively defined the aroma signatures of spice-smoked wings. Spice-specific aroma enrichment and sensory properties were evident: rosemary intensified woody–spicy notes, mint enhanced herbal freshness, and rose amplified floral attributes. The proposed method demonstrated advantages in safety, ease of use, and flavor customization, aligning with clean-label trends and supporting innovation in home-based culinary practices. Moreover, it facilitates the tailored modulation of smoked meat flavor profiles, thereby enhancing product differentiation and broadening consumer acceptance.